Crazy‐paving patterns as rare radiological manifestations of pulmonary cryptococcosis: a case report - He Yu; Kaige Wang; Dong Huang; Lu Wen; Ying Zhang; Ye Wang; Yongjiang Tang; Jiajia Dong; Zongan Liang (BMC Pulmonary Medicine, 2021)
Abstract Background Crazy-paving patterns are rarely reported as radiological manifestations of pulmonary cryptococcosis. Case presentation Herein, we presented a very rare case of a crazy-paving pattern as a radiological manifestation of pulmonary cryptococcosis in a patient with primary ciliary dyskinesia. The diagnosis of pulmonary cryptococcosis and primary ciliary dyskinesia was ultimately confirmed by bronchoscopic biopsy, fungus culture, whole exome sequencing of blood, etc. The patient received flucytosine (PO, 5 g per day) and amphotericin B (IV, 70 mg per day) during hospitalization and sequential therapy with voriconazole (PO, 200 mg twice a day) after discharge. He recovered during follow-up. Conclusions We concluded that pulmonary cryptococcosis should be considered a possible cause of crazy-paving patterns in chest CT scans.